A STUDY OF CONSUMER PREFERENCES TOWARDS MOBILE STORES - Sharma, Dr. Gargi; Sharma, Mr. Rohan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The mobile phones are an essential part of consumers’ life. The shopping of various products and services are carried out through mobile phones. Mobile devices offer opportunities to combine information search, phone functionality and interaction while shopping in-store or using a product. A mobile device is a constant companion to the consumer, a gateway to a relationship between the consumer and the retailer, making it an ideal supplementary channel for distance selling and physical retailing. The purchasing of mobile phones through mobile stores is now declined after the introduction of online shopping platforms. The present study is an attempt to identify the consumer preferences towards mobile stores, the factors affecting their decision making and analysis of their satisfaction.